Alveolar Echinococcosis in Children - Emilija Jonaitytė; Martynas Judickas; Eglė Tamulevičienė; Milda Šeškutė (Hindawi Limited, 2020)
Alveolar echinococcosis (AE) is an infectious zoonotic disease that is caused by Echinococcus multilocularis. The disease is generally identified accidentally because of the long asymptomatic period, has a malignant behaviour, and mainly occurs in the liver. Usually it is diagnosed in adults and is very rare in pediatric patients. We report two cases of AE and 1 differential case between AE and cystic echinococcosis (CE) in children: two of them had lesions in the liver and one had rare extrahepatic presentation of a cyst in the spleen. All our patients received chemotherapy with albendazole because surgical treatment was not recommended. The children were followed-up from 10 to 30 months and no significant improvement was seen. In this report we discuss the difficulties we faced in the treatment and follow-up of these patients. We also review the main clinical manifestations, general diagnostic methods, and treatment options of AE according to the current literature.